Transformasi Dan Problematika Pendidikan Agama Islam Pada Perguruan Tinggi di Era Disrupsi - St Wikowati; Hafid Effendy, Moh.; Gilang Ramadhan Al-Haris, Nur (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the transformation and challenges of Islamic Religious Education (PAI) in higher education amid the disruptions brought by the Society 5.0 era. The research employs a qualitative method with a literature review approach by examining contemporary scholarly publications and policy documents related to Islamic education and technological development. The findings reveal that PAI in higher education faces several significant challenges, including limited digital competence among lecturers, inadequate technological infrastructure, and a curriculum that is not yet fully responsive to rapid socio-technological changes. These conditions lead to learning processes that are less integrative between scientific knowledge and Islamic values. The study also highlights the need for curriculum reform that emphasizes the balance between faith, knowledge, practice, and character, supported by adaptive learning models such as blended learning, digital platforms, and artificial intelligence. Strengthening the digital and pedagogical competence of lecturers is essential to ensure effective and relevant learning. The study concludes that multi-stakeholder collaboration is crucial to advance Islamic education in preparing a generation that is intelligent, adaptive, and possesses strong ethical integrity in the digital era.